2015
DOI: 10.4103/2228-7477.161463
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of blood glucose concentration in type 1 diabetics using single order sliding mode control combined with fuzzy on-line tunable gain, a simulation study

Abstract: Diabetes is considered as a global affecting disease with an increasing contribution to both mortality rate and cost damage in the society. Therefore, tight control of blood glucose levels has gained significant attention over the decades. This paper proposes a method for blood glucose level regulation in type 1 diabetics. The control strategy is based on combining the fuzzy logic theory and single order sliding mode control (SOSMC) to improve the properties of sliding mode control method and to alleviate its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…Other FL approaches have been tested using virtual patients or simulations [ 20 - 24 ]. For example, Miller et al reported a fuzzy controller combined with a learning algorithm that extracted initial patient profiles using open-loop data [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other FL approaches have been tested using virtual patients or simulations [ 20 - 24 ]. For example, Miller et al reported a fuzzy controller combined with a learning algorithm that extracted initial patient profiles using open-loop data [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…For example, Miller et al reported a fuzzy controller combined with a learning algorithm that extracted initial patient profiles using open-loop data [ 23 ]. Another example was provided by Dinani et al [ 24 ], who suggested combining fuzzy and sliding-mode controllers, with the goal of using feedback to govern the insulin delivery rate more aggressively.…”
Section: Resultsmentioning
confidence: 99%
“…According to a recent study from the World Health Organization and the international diabetes federation, there are around 463 million diabetes cases worldwide [ 1 , 2 ]. Generally, diabetes results when the pancreas is not able to produce enough insulin, or the latter is not effectively delivered to the cells.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, deficient production and inefficient use of insulin cause diabetes type 1 and type 2, respectively. When the blood sugar level is less than 70 mg/dL, the situation is called hypoglycemia [ 2 ]. Conversely, it is called hyperglycemia when the blood sugar level is more than 120 or 180 mg/dL when fasting or after meals, respectively [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Now, the nonlinear control techniques designed for the closed-loop AP system include; SMC approach presented in [24], provides a robust glucose regulation but the state unavailability and chattering phenomenon challenge its candidature to AP mechanism. Few synergistic strategies of fuzzy logics and SMC were focused in [25], [26]. However, these techniques required a long settling time and often degraded in uncertain situations.…”
Section: Introductionmentioning
confidence: 99%